Relative cubulations and groups with a 2-sphere boundary. (24th April 2020) - Einstein, Eduard; Groves, Daniel
Abstract : We introduce a new kind of action of a relatively hyperbolic group on a CAT(0) cube complex, called a relatively geometric action. We provide an application to characterize finite-volume Kleinian groups in terms of actions on cube complexes, analogous to the results of Markovic and Haïssinsky in the closed case.